2022
DOI: 10.7150/ijbs.64187
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline improves the functional recovery after traumatic brain injury via inhibition of aquaporin-4

Abstract: Traumatic brain injury (TBI) is one of the main concerns worldwide as there is still no comprehensive therapeutic intervention. Astrocytic water channel aquaporin-4 (AQP-4) system is closely related to the brain edema, water transport at blood-brain barrier (BBB) and astrocyte function in the central nervous system (CNS). Minocycline, a broad-spectrum semisynthetic tetracycline antibiotic, has shown anti-inflammation, anti-apoptotic, vascular protection and neuroprotective effects on TBI models. Here, we tried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…AQP4 is the most abundant water channel protein and is primarily responsible for water homeostasis of the CNS [ 66 ]. Several studies have reported that inhibition of AQP4 could significantly ameliorate edema and BBB disruption, reduce glial responses and neuronal apoptosis after CNS injury and neurodegenerative diseases [ 67 , 68 ]. AQP4 could also directly ameliorate severe atrophy and retrograde the degeneration of rubrospinal neurons after SCI [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…AQP4 is the most abundant water channel protein and is primarily responsible for water homeostasis of the CNS [ 66 ]. Several studies have reported that inhibition of AQP4 could significantly ameliorate edema and BBB disruption, reduce glial responses and neuronal apoptosis after CNS injury and neurodegenerative diseases [ 67 , 68 ]. AQP4 could also directly ameliorate severe atrophy and retrograde the degeneration of rubrospinal neurons after SCI [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] Increased AQP4 expression leading to excessive water influx is implicated in astrocyte swelling in pathological conditions such as cerebral edema and traumatic brain injury. [ 57 , 58 , 59 ] Thus, peripheral nerve injury may activate NFAT5‐AQP4 signaling, culminating in astrocyte swelling in the SDH.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline is known as a second-generation and semi-synthetic tetracycline antibiotic. Minocycline is quickly absorbed into the body, penetrates the BBB, and affects many biological actions (differing from its antibiotic action) both in vivo and in vitro , including the following: attenuation of BBB breakdown by inhibiting the production of matrix metalloproteinase-9; functional improvement after traumatic brain injury via suppression of aquaporin-4 production; relieve white matter injury in the neonatal rat brain by suppression of IL-1β and TNF-α production; neuroprotection from ischemic brain damage; alleviation of LPS-induced depressive-like behavior; and suppression of NOx production in cultured microglia under hypoxia ( 55 , 56 ). In our study, we demonstrated that intraperitoneal pretreatment with minocycline (20 mg/kg/day, 3 consecutive days) attenuated poly I:C-induced IL-1β mRNA expression in rat brain, transient fever, and decrease in locomotor activity ( 57 ).…”
Section: Treatments For Neuroinflammationmentioning
confidence: 99%